Atherosclerotic Plaque Imaging: Coronaries - Rashid, Imran; Kim, W. Yong; Prieto, Claudia; Makowski, Marcus R.; Manning, Warren J.; Botnar, René M. (Elsevier, 2018)
Advances in coronary magnetic resonance angiography (CMRA) have yielded improvements in spatial resolution and image acquisition times, highlighting the potential of CMR for comprehensive coronary assessment without the need for ionizing radiation. In addition to plaque burden, noncontrast CMR can provide important information regarding plaque characteristics, such as the presence of thrombus or intraplaque hemorrhage, through the T1-shortening effect of methemoglobin that has proven prognostic utility. Furthermore, contrast-enhanced CMR and molecular imaging using hybrid positron emission tomography and MRI (PET-MR) systems have the potential to identify active cellular and molecular processes that drive atherosclerotic disease progression. These may allow for the precise risk stratification of individuals with subclinical disease in addition to the identification of novel therapeutic targets. Despite challenges, the quality and feasibility of coronary magnetic resonance imaging continues to improve, and its eventual use in combination with MR perfusion, viability, and functional imaging raises the enticing prospect of comprehensive, single modality assessment of patients with ischemic heart disease.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Coronary artery disease; Coronary artery imaging; Magnetic resonance imaging